Pengembangan Bahan Ajar Pendidikan Agama Islam Berbasis Media Audiovisual pada Kelas X SMA 2 Magetan - Munawaroh, Nurul Latifah (Social Science Academic, 2023)
This study aims to develop Teaching Materials for Islamic Religious Education Based on Audiovisual Media in class X at SMA Negeri 2 Magetan with honesty material, and to find out how the level of validity, practicality and effectiveness of these teaching materials is. The use of this media is very helpful for teachers in the teaching and learning process in class, not only that but the media is also an integral part of a teaching and learning activity. This research was conducted using a 4-D model consisting of definition, design, development, and deployment. Which was modified to 3-D with three stages, namely defining, designing, and developing which were carried out for students in class X IPA 7. The research instruments used were media validation sheets, student response questionnaires and tests. learning outcomes and data are then analyzed using descriptive analysis. The implication of this research is for educators, it can help in teaching Islamic Religious Education material more easily and more effectively. In addition, educators are more helpful in activating students to engage in learning. For students, it can make it easier to understand Islamic Religious Education material more interestingly. And for future researchers to provide more theories from experts regarding media.